أثر اختلاف نمط المنظم التمهيدي المستخدم في برامج الكمبيوتر متعددة الوسائل على تحصيل طلاب شعبة تكنولوجيا التعليم المستقلين والمعتمدين ومستوى أدائهم العملى فى مقرر الكمبيوتر - حسين، عمرو جلال الدين أحمد (2000)
Reviewing the curricula at the faculties of education revealed that there aren’t any courses for teaching multimedia technology which aims at preparing teachers in all departments for. However, multimedia laboratories Which are available in many schools and faculties , will be Used in all educational institutions in the near future?. The problem of this study can be stated in the following questions : 1- what is the effect of changing the order of examples and analogies used for teaching multimedia technology concepts ( positive example – negative example – analogy ) ; (positive example – analogy – negative example ) ; ( analogy – positive example – negative example ) in multimedia computer programs on : a) prospective teachers’ immediate achievement of multimedia technology concepts ? b) prospective teachers’ delayed achievement of multimedia technology concepts ? c) the time that prospective teachers take to answer an achievement test of multimedia technology concepts ? 2- what is the effect of the cognitive style ( field dependent versus field independent ) on : a) prospective teachers immediate achievement of multimedia technology concepts through multimedia computer programs ? b) prospective teachers delayed achievement of multimedia technology concepts through multimedia computer programs ? c) the time that prospective teachers take to answer an achievement test of multimedia technology concepts ? 3- what is the effect of the interaction between changing the order of presenting examples and analogies in multimedia computer programs and the cognitive style of prospective teachers on : a) their immediate achievement of multimedia technology concepts ? b) their delayed achievement of multimedia technology concepts ? c) the time they take to answer an achievement test of multimedia technology concepts ? Purpose of the Study ; the purpose of this study was fourfold : 1- Determining the multimedia technology concepts that prospective teachers at the faculties of education should acquire before finishing their study. 2- Using these concepts for designing a multimedia computer program so as to investigate the effect of changing the order of examples (positive versus negative) and analogies used for presenting multimedia concepts, and the cognitive style of students on their immediate and delayed achievement of multimedia technology concepts and the Time They Take to Answer the Immediate Achievement Test. 3- Familiarizing prospective teachers at the faculties of education of the concepts related to multimedia technology and the appliances required for producing and using it for developing The educational Process. Significance of the Study : 1- This study may guide those in charge at the faculties of education to Using multimedia technology concepts that prospective teachers Should acquire before they finish their university education. 2- This study may help in determining to what extent using the multimedia technology is effective in abolishing the illiteracy of multimedia technology and its related concepts. 3- This study may help in increasing the effectiveness of multimedia computer programmes presented to students at the faculties of education through determining the design variables necessary for these programmes. 4- This study may help in finding out the relationship between the variables of designing multimedia technology and the cognitive style . Limitations of the Study : 1- Experimentation was confined to multimedia technology concepts that jury members recommended as necessary to be acquired by prospective teachers at the faculties of education . 2- Computer sets trade mark (IBM) and Compatible that work on multimedia computer programmes were used for presenting the multimedia programme. 3- Factors related to students specialization were disregarded . Hypotheses of the Study : 1- There will be significant differences at the .05 level of Significant between the means scores obtained by the student the teachers on the immediate achievement test of multimedia technology concepts attributed to the effect of the order of presenting examples and analogies. 2- There will be significant differences at the .05 level of Significant between the means scores obtained by the student teachers on the detlayed achievement test of multimedia technology concepts attributed to the effect of the type of the cognitive style . 3- There will be significant differences at the .05 level of Significant between the means scores obtained by the student teachers on the immediate achievement test of multimedia technology concepts test attributed to the effect of the interaction between the order of presenting examples , analogies and the type of the cognitive style. 4- There will be significant differences at the .05 level of Significant between the means scores obtained by the student teachers on the delayed achievement test of multimedia technology concepts attributed to the effect of presenting examples and analogies. 5- There will be significant differences at the .05 level of Significant between the means scores obtained by the student teachers on the delayed achievement test of multimedia technology concepts attributed to the effect of the type of cognitive style . 6- There will be significant differences at the .05 level of Significant between the means scores obtained by the student teachers on the delayed achievement test of multimedia technology concepts attributed to the effect of the interaction between the order of presenting concepts, analogies and the type of cognitive style . 7- There will be significant differences at the .05 level of Significant between the mean time taken by the student teachers to an achievement test of multimedia technology attributed to the order of presenting examples and analogies. 8- There will be significant differences at the .05 level of Significant between the mean time taken by the student teachers to answer an achievement test of multimedia technology concepts attributed to the effect of the type of the cognitive style. 9- There will be significant differences at the .05 level of Significant between the mean time taken by the student teachers to answer an achievement test of multimedia technology concepts attributed to the effect of the interaction between the order of presenting examples, analogies and the type of cognitive style. Method : The experimental method was utilized in this study. The Experimental Design: This study utilized the experimental design known as "3x2 Factorial Design ". Treatment Materials A suggested multimedia technology unit consisting of four educational computer programmes represented the treatment materials of the study. Sample: a) The subjects of this study were 59 students randomly selected representing all departments at the Faculty of Education , Al – Azhar University in Cairo . Variables of the Study : Independent Variables : 1) The order of presenting examples and analogies; Such a Variable had three levels : a) Positive example , negative example , and analogy. b) Positive example, analogy, and negative example. c) Analogy , positive example , and negative example. 2- The cognitive style; Such a Variable had two levels : a) Field dependent b) Field independent Dependent Variables : 1- The immediate achievement of multimedia technology concepts 2- The delayed achievement of multimedia technology concepts 3- The time used for answering the achievement test. Mediator Variables : 1- The content of the programs. 2- The number of examples in each of the three programs . 3- The type of navigation used 4- The type of appliances used in the experiment . Resuls of the study: 1- There were no significant differences at the .05 level of Significant between the means scores obtained by the student teachers on the immediate achievement test of multimedia technology concepts attributed to the effect of the order of presenting examples and analogies. 2- There were no significant differences at the .05 level of Significant between the means scores obtained by the student teachers on the delayed achievement test of multimedia technology concepts attributed to the effect of the order of presenting examples and analogies. 3- There were significant differences at the .05 level of Significant between the Time taken by the student teachers to answer an achievement test of multimedia technology concepts attributed to the effect of the order of presenting examples and analogies. 4- There were no significant difference at the .05 level of Significant between the mean scores of the student teachers on the immediate achievement test of multimedia technology concepts attributed to the effect of the cognitive style. 5- There was a significant difference at the .05 level of Significant between the mean sores of the student teachers on the delayed achievement test of multimedia technology concepts attributed to the effect of the cognitive style 6- There was a significant difference at the.05 level of Significant between the mean time taken by the student teachers to answer an achievement test of multimedia technology concepts attributed to the effect of the cognitive style. 7- There were no significant differences at the .05 level of Significant between the means scores of the student teachers on the immediate achievement test of multimedia technology concepts attributed to the interaction between the order of presenting examples, analogies and the cognitive style. 8- There were no significant differences at the .05 level of Significant between the means scores of the student teachers on the delayed achievement test of multimedia technology concepts attributed to the interaction between the order of presenting examples, analogies and the cognitive style. 9- There were significant differences at the .05 level of Significant between the mean time taken by the student teachers to answer an achievement test of mult